A GIS-based Fuzzy-AHP method for the evaluation of solar farms locations: Case study in Khuzestan province, Iran. (October 2017) - Asakereh, Abbas; Soleymani, Mohsen; Sheikhdavoodi, Mohammad Javad
Highlights: The manuscript provides a useful method to evaluate solar farms. The manuscript applied GIS along with a Fuzzy Logic and the Analytic Hierarchy Process (AHP) technique to prioritize the land of Khuzestan province in Iran to install solar photovoltaic farms. The manuscript suggests that by using solar power facilities for multipurpose application (generating solar power and combating with desertification), the costs of solar power generation will amortize and the overall cost will reduce. Abstract: This study was conducted to prioritize the land of Khuzestan province in Iran to install solar photovoltaic farms, based on techno-economic and environmental aspects. Fuzzy logic and fuzzy membership functions were used to create criteria layers in the environment of GIS to draw the map of the suitability of lands. Also the Analytic Hierarchy Process (AHP) technique was used to weigh the techno-economic and environmental criteria and to draw the final map of the suitability of lands as solar farms. Results showed that Khuzestan province has a great potential to generate solar electricity via photovoltaic arrays. Based on the results, the potential of solar electricity generation in Khuzestan through the worst scenario is approximately 1.75 times more than the gross electricity produced in Iran in 2013. On the other hand, installing solar farms on the lands located at the south and the southwest of the province which are in danger of turning to desert, is a good opportunity to combat with the spread of desertification. By using solar power facilities for multipurpose application (generating solar power and combating with desertification), the costs of solar power generation will be amortized and the overall cost of solar power will be reduced. Based on the map of the suitability of the lands as solar farm, the desert and semi-desert areas of Khuzestan province have the excellent potential of electricity generation.